2014
DOI: 10.1039/c4tc00969j
|View full text |Cite
|
Sign up to set email alerts
|

Particle tuning and modulation of the magnetic/colour synergy in Fe(ii) spin crossover-polymer nanocomposites in a thermochromic sensor array

Abstract: A particle size control of the [Fe(NH2Trz)3](BF4) spin crossover material is reached, with its associated thermochromism determined with a photographic digital camera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…In the SCO field polymer and (to a lesser extent) inorganic matrices have been extensively used for various aims, including the dispersion of molecules to obtain diluted, noninteracting systems in solid matrices, the processing of SCO materials to fabricate coatings and other functional composite materials and, more recently, to investigate matrix–particle interactions either from a fundamental point of view or to develop useful synergies between the constituents . From the experimental point of view it was shown that depending on the physico‐chemical properties of the matrix (e.g., stiffness, chemical affinity, etc.)…”
Section: Size Reduction Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the SCO field polymer and (to a lesser extent) inorganic matrices have been extensively used for various aims, including the dispersion of molecules to obtain diluted, noninteracting systems in solid matrices, the processing of SCO materials to fabricate coatings and other functional composite materials and, more recently, to investigate matrix–particle interactions either from a fundamental point of view or to develop useful synergies between the constituents . From the experimental point of view it was shown that depending on the physico‐chemical properties of the matrix (e.g., stiffness, chemical affinity, etc.)…”
Section: Size Reduction Effectsmentioning
confidence: 99%
“…At the nanoscale these phenomena can be accentuated and eventually new phenomena (e.g., coherent particle transformation) may emerge. While these important kinetic effects have been rarely discussed in the SCO literature, the hypothesis of matrix‐mediated particle–particle interactions has been several times evoked to account for large hysteresis in SCO nanomaterials . For the moment theoretical analysis on the effectiveness of such interactions is missing.…”
Section: Size Reduction Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplicity of the optical detection of the usually LS-red HS-white and the associated magnetic 40 changes for iron(II) SCO compounds stimulate the interest for potential information storage, 5 , 6 display devices, 2,6 and sensors. 7,8,9,10,11,12 The iron complexes of hydrotris(pyrazolyl)borato ligands exhibit such a SCO phenomenon between LS-red HS-white 45 states 13,14,15,16,17,18,19 and the transition temperatures (T 1/2 ) were found to vary strongly with the substituents on the pyrazolyl rings or on the boron atom. 18,20 The interplay of the steric effects of substituents with the different sizes of the LS and HS Fe(II) ions was demonstrated to be the decisive factor in controlling the 50 relative stability of the spin states.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] The spin-crossover phenomenon may appear in systems in which states with different spin have similar electronic energies. [14][15][16][17][18] An intermediate point between mononuclear spin-crossover systems and spin-crossover frameworks can be found in polymeric complexes including two or more metal centers able to undergo a spin transition. 2 Although thermal spin-crossover is by far the most studied way of inducing the transition, spincrossover can also be controlled by means of external pressure, electromagnetic radiation (light) and electric fields.…”
Section: Introductionmentioning
confidence: 99%